Use of value management workshops and critical success factors in introducing local experience on the International construction projects - Surlan, Nebojsa; Cekic, Zoran; Torbica, Zeljko (Journal of Civil Engineering and Management, 2016)
Critical success factors can be used in value management workshops to determine the client value system, which in turn is critically important to the briefing process and the successful delivery of construction projects. This research is concerned with international construction projects. In particular, it investigates the impact of local knowledge on the client value system. Workshops were organised on 12 international projects in the western Balkans region. The initial client value system was captured by   using a paired comparison exercise. Next, local knowledge information was introduced, and the EFTE (Estimate-Feedback-Talk-Estimate) technique was used to capture the revised client value system. The changes in the two sets of client value systems were analysed. The results indicate that 4 parameters (Scope, Contract-admin, Human resources and Health and Safety) out of 8 changed and that the changes were statistically significant. Local knowledge can be used to impact client value system.First published online: 16 Dec 2015